ANALISIS ASPEK PEMENUHAN TOKOH SUKAB DALAM NOVEL SEPOTONG SENJA UNTUK PACARKU KARYA SENO GUMIRA AJIDARMA (KAJIAN TEORI HUMANISTIK ABRAHAM MASLOW) - Lony Felianda Saputri (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
The novel Sepotong Senja Untuk Pacarku by Seno Gumira Ajidarma includes 16 short story compositions regarding dusk that bind together reflection stories about life which are written in an absurd and unique style by the author. Based on this, this novel has its own charm to be studied further by implementing a literary psychology approach based on Abraham Maslow's humanistic theory because it is closely related to reality which includes the depth of human nature, conscience, changes in attitudes and changes in mindset. The formulation of the problem in this study is how the concept of the hierarchy of needs and the form of its fulfillment for the Sukab character in the novel Sepotong Senja Untuk Pacarku is based on the humanistic psychology aspect of Abraham Maslow and how the Sukab character self-actualizes based on the study of Abraham Maslow's humanistic psychology. This type of research uses a qualitative descriptive method. Descriptive is stated because in this study the researcher describes the data to be analyzed in the form of the psychological aspect of the character Sukab in the novel Sepotong Senja Untuk Pacarku by Seno Gumira Ajidarma based on the study of humanistic psychology of Abraham Maslow. Data collection techniques used in this research are literature study techniques and note-taking techniques. Based on the results of the research, in the novel Sepotong Senja Untuk Pacarku, it is found that several aspects of multilevel needs include physiological needs, security needs, love and belonging needs, self-esteem needs and self-actualization. Keywords : literary psychology, humanistic, hierarchy of needs